Automated class diagram elicitation using intermediate use case template - Shweta; Ratna Sanyal; Bibhas Ghoshal (IET Software)
Abstract Class diagrams, being more illustrative, provide an easier way of understanding software requirements compared to use case descriptions. Both manual and automated methods are used for the extraction of class diagrams from requirements. The automated techniques employ certain extraction rules and natural language processing methods. Each use case description template introduces a small set of extraction rules. However, when all types of templates are considered, the number of rules becomes large and the procedure becomes tedious. Thus, researchers restricted the class diagram extraction procedure to some specific use case description templates. However, such a restriction negatively affects the software developers as they get restricted to working with only limited templates. The proposed work in this paper strives to remove this restriction on developers by introducing an intermediate template. The traditional use case description templates get transformed into the intermediate template and the rule extraction procedure is then applied to this intermediate template. This reduces the total number of extraction rules and hence, brings down the extraction complexity. The class diagrams extracted from use case description templates of different domains using proposed technique show more accuracy in terms of completeness and correctness when compared with the state of the art approaches.